2012
DOI: 10.1007/s11356-012-1238-9
|View full text |Cite
|
Sign up to set email alerts
|

One-year measurements of chloroethenes in tree cores and groundwater at the SAP Mimoň Site, Northern Bohemia

Abstract: Chlorinated ethenes (CE) are among the most frequent contaminants of soil and groundwater in the Czech Republic. Because conventional methods of subsurface contamination investigation are costly and technically complicated, attention is directed on alternative and innovative field sampling methods. One promising method is sampling of tree cores (plugs of woody tissue extracted from a host tree). Volatile organic compounds can enter into the trunks and other tissues of trees through their root systems. An analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…This behavior correlated well with groundwater level fluctuations (higher levels in winter), but other studies also point toward possible volatilization loss in summer due to high temperatures (e.g., Vroblesky ; Holm and Rotard ). The high monthly variations of concentrations in tree cores observed by Wittlingerova et al () do not indicate long‐term storage of chlorinated ethenes in wood. Model simulations (Trapp ) yield half‐lives for loss by volatilization from stems between three weeks (TCE, summer conditions) and about 3 months (PCE, winter) which means each tree core sample (typically between 5 and 10 cm in length) integrates the GW concentration of several weeks but most likely not over longer periods.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This behavior correlated well with groundwater level fluctuations (higher levels in winter), but other studies also point toward possible volatilization loss in summer due to high temperatures (e.g., Vroblesky ; Holm and Rotard ). The high monthly variations of concentrations in tree cores observed by Wittlingerova et al () do not indicate long‐term storage of chlorinated ethenes in wood. Model simulations (Trapp ) yield half‐lives for loss by volatilization from stems between three weeks (TCE, summer conditions) and about 3 months (PCE, winter) which means each tree core sample (typically between 5 and 10 cm in length) integrates the GW concentration of several weeks but most likely not over longer periods.…”
Section: Discussionmentioning
confidence: 72%
“…TCE may have been present in the volume available to the roots, but not in the samples taken by the DP sampling. Moreover, DP sampling relies on the concentration of contaminant present at the time of sampling, while trees integrate over weeks or even months (Trapp ; Wittlingerova et al ). The length of the tree cores was 5 cm, which is in agreement with recent suggestions (Holm et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoscreening studies have shown that concentrations of chlorinated ethenes in trees vary in all three dimensions (Vroblesky et al ; Holm and Rotard ; Limmer et al ). Further, seasonal variation in contaminant concentrations has been observed, where concentrations increased with increasing transpiration (Limmer et al ) and increasing groundwater level (Wittlingerova et al ). Transpiration is positively correlated with environmental conditions such as temperature and hours of sunshine, and negatively correlated with the relative air humidity (Stern ).…”
Section: Introductionmentioning
confidence: 99%
“…The lighter and less hydrophobic degradation products (Cwiertny and Scherer ) thus have a shorter residence time within the trees than the parent compounds. The best sampling time for detection of PCE and TCE in trees is after a period with high uptake of contaminated water and low diffusional loss from the tree due to decreased temperatures, resulting in high concentrations in the trees (Wittlingerova et al ). Since cis‐DCE and VC have considerable lower residence time in the tree trunk (the half‐times of loss from the stem are: PCE = 5.6d, TCE = 6.65d, cis‐DCE = 3.72d, and VC = 0.25d – calculated by the model of Trapp using the original parameters), their presence in wood is more likely to be dependent on uptake at the time of tree core sampling.…”
Section: Introductionmentioning
confidence: 99%